Plankton community respiration and bacterial metabolism in a North Atlantic Shelf Sea during spring bloom development (April 2015). (October 2019) - García-Martín, E. Elena; Daniels, Chris J.; Davidson, Keith; Lozano, Jose; Mayers, Kyle M.J.; McNeill, Sharon; Mitchell, Elaine; Poulton, Alex J.; Purdie, Duncan A.; Tarran, Glen A.; Whyte, Callum; Robinson, Carol
Highlights: We present temporal evolution of plankton metabolism at short temporal scales (≤5 days). Concurrent increase in primary production and plankton community respiration during a bloom event. Free-living bacteria are not the major producers of CO2 . Locally synthesized organic carbon sufficient to fulfil bacterial carbon demand in euphotic waters. Bacterial growth efficiency varied during the evolution of the spring bloom. Abstract: Spring phytoplankton blooms are important events in Shelf Sea pelagic systems as the increase in carbon production results in increased food availability for higher trophic levels and the export of carbon to deeper waters and the sea-floor. It is usually accepted that the increase in phytoplankton abundance and production is followed by an increase in plankton respiration. However, this expectation is derived from field studies with a low temporal sampling resolution (5–15 days). In this study we have measured the time course of plankton abundance, gross primary production, plankton community respiration, respiration of the plankton size classes (>0.8 µm and 0.2–0.8 µm) and bacterial production at ≤5 day intervals during April 2015 in order to examine the phasing of plankton autotrophic and heterotrophic processes. Euphotic depth-integrated plankton community respiration increased five-fold (from 22 ± 4 mmol O2 m −2 d −1 on 4th April to 119 ± 4 mmol O2 m −2 d −1 on 15th April) at the same time as gross primary production also increased five-fold, (from 114 ± 5 to 613 ± 28 mmol C m −2 d −1 ). Bacterial production began to increase during the development of the bloom, but did not reach its maximum until 5 days after the peak in primary production and plankton respiration. The increase in plankton community respiration was driven by an increase in the respiration attributable to the >0.8 µm size fraction of the plankton community (which would include phytoplankton, microzooplankton and particle attached bacteria). Euphotic depth-integrated respiration of the 0.2–0.8 µm size fraction (predominantly free living bacteria) decreased and then remained relatively constant (16 ± 3 – 11 ± 1 mmol O2 m −2 d −1 ) between the first day of sampling (4th April) and the days following the peak in chlorophyll- a (20th and 25th April). Recent locally synthesized organic carbon was more than sufficient to fulfil the bacterial carbon requirement in the euphotic zone during this productive period. Changes in bacterial growth efficiencies (BGE, the ratio of bacterial production to bacterial carbon demand) were driven by changes in bacterial production rates increasing from <30 ± 14% on 4th April to 51 ± 11% on 25th of April. This study therefore shows a concurrent rather than a phased increase in primary production and community respiration attributable to cells >0.8 µm during the development of the spring bloom, followed 5 days later by a peak in bacterial production. In addition, the size fractionated respiration rates and high growth efficiencies suggest that free living bacteria are not the major producers of CO2 before, during and a few days after this shelf sea spring phytoplankton bloom.